Seismic Protection of Laboratory Contents: The UC Berkeley Science Building Case Study - Mary C. Comerio (University of California, Institute of Urban and Regional Development (IURD), 2003)
The research described in this report is a part of the Disaster Resistant University (DRU) initiative funded by the Federal Emergency Management Agency (FEMA) and the University of California, Berkeley. The first phase of the Disaster Resistant University initiative produced a study of potential earthquake losses at U.C. Berkeley together with an analysis of the economic impacts. In that report, Comerio (2000) found that despite the extraordinary building retrofit program, the U.C. Berkeley campus remained vulnerable to losses from nonstructural failures and losses in highly concentrated research facilities. This report is focused on strategies for improving seismic performance for laboratory furnishings and equipment. This report describes a case study of a biology laboratory building and its contents, used as a basis for developing damage mitigation strategies and cost estimates. The data developed here were also used by researchers at the Pacific Earthquake Engineering Research (PEER) Center for the development of loss estimates and for the development of models for performance-based engineering (U.C. Science Testbed Committee, 2002), as well as for a technical manual on retrofitting laboratory contents (Holmes and Comerio, 2003).
Keywords: 330